Auricular Acupuncture for Exam Anxiety in Medical Students-A Randomized Crossover Investigation. - Catharina Klausenitz; Henriette Hacker; Thomas Hesse; Thomas Kohlmann; Karlhans Endlich; Klaus Hahnenkamp; Taras Usichenko (PLoS ONE, 2016)
Auricular acupuncture (AA) is effective in the treatment of preoperative anxiety. The aim was to investigate whether AA can reduce exam anxiety as compared to placebo and no intervention. Forty-four medical students were randomized to receive AA, placebo, or no intervention in a crossover manner and subsequently completed three comparable oral anatomy exams with an interval of 1 month between the exams/interventions. AA was applied using indwelling fixed needles bilaterally at points MA-IC1, MA-TF1, MA-SC, MA-AT1 and MA-TG one day prior to each exam. Placebo needles were used as control. Levels of anxiety were measured using a visual analogue scale before and after each intervention as well as before each exam. Additional measures included the State-Trait-Anxiety Inventory, duration of sleep at night, blood pressure, heart rate and the extent of participant blinding. All included participants finished the study. Anxiety levels were reduced after AA and placebo intervention compared to baseline and the no intervention condition (p < 0.003). AA was better at reducing anxiety than placebo in the evening before the exam (p = 0.018). Participants were able to distinguish between AA and placebo intervention. Both AA and placebo interventions reduced exam anxiety in medical students. The superiority of AA over placebo may be due to insufficient blinding of participants.